The Effect of Acupressure at the 3rd Point of liver Channel on Quality of Life of Female Students with Primary Dysmenorrhea in Tehran Teacher Training Center in 2008: A Randomize Clinical Trial - f Bazarganipour (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Dysmenorrhea affects women’s quality of life; moreover it results in physical, mental, social and economical problems. The aim of this study was to evaluate the effect of acupressure at the third point of liver channel (liv3) on quality of life in female students of Tehran Teaching Training (Tarbiat Moallem) Center with primary dysmenorrhea. Methods: This single-blind randomized clinical trial was conducted on 194 female students of Nasibeh Tarbiat Moallem center in Tehran who had had inclusion criteria. In the first cycle, the severity and duration of pain and quality of life were determined. Therefore, the participants were randomly assigned to either experimental or control group. In the second, third and fourth cycles, acupressure at liv3 and placebo point during 3-7 days before menstruation for 20 minute were carried out. In the fourth cycle, participants completed SF-36 questionnaire after menstruation again. Data-gathering Instruments used in this study included wrong-Baker faces pain scale,Beck-21 questionarre, SF-36 questionnaire, clock, Acuhealth tens pro 900 set, force guage. Data were analyzed with SPSS 16 and x2 test, Man Whitney U, independent and paired test. P values were set as 0.05(p<0.05). Results: There was no significant difference in mean quality of life dimension between two groups in the first cycle (p>0.05) but there was a significant difference in mean quality of life dimension between two groups in the fourth cycle (p<0.05). The comparison between the first and the fourth cycle in two group showed a significant difference in all dimension (p<0.05) but there was not any significant difference between two cycles in Role Emotional functioning dimension in experimental group (p>0.05). Moreover, there was no significant difference between two cycles in Role Emotional functioning and social functioning dimensions in experimental group (p>0.05). Conclusion: with regard to the results of this study, acupressure at liv3 point is suggested as useful, effective, cheap and available treatment for primary dysmenorrhea.